2014
DOI: 10.1371/journal.pone.0100505
|View full text |Cite
|
Sign up to set email alerts
|

A Novel p. Gly630Ser Mutation of COL2A1 in a Chinese Family with Presentations of Legg–Calvé–Perthes Disease or Avascular Necrosis of the Femoral Head

Abstract: ObjectiveMutations in the type II collagen gene are associated with certain human disorders, collectively termed type II collagenopathies. They include Legg–Calvé–Perthes disease (LCPD) and avascular necrosis of the femoral head (ANFH). These two diseases are skeletal dysplasias, inherited in an autosomal dominant fashion, characterized by groin pain, dislocation of the hip and diminished joint mobility. Coxa vara and elevation of the greater trochanter of the femur comprise the typical phenotype of LCPD, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 22 publications
0
50
0
1
Order By: Relevance
“…For example, 20 patients with Legg-Calvé-Perthes disease were included in this study because some reports have indicated that a type II collagenopathy manifests as this entity. 21,22 However, most of them did not show any sequence variant through TES. Second, some patients might have had skeletal dysplasia due to a causative gene that has not yet been discovered and is therefore not on the TES gene list.…”
Section: Discussionmentioning
confidence: 93%
“…For example, 20 patients with Legg-Calvé-Perthes disease were included in this study because some reports have indicated that a type II collagenopathy manifests as this entity. 21,22 However, most of them did not show any sequence variant through TES. Second, some patients might have had skeletal dysplasia due to a causative gene that has not yet been discovered and is therefore not on the TES gene list.…”
Section: Discussionmentioning
confidence: 93%
“…We limited the target of WES to neither‐associated ONFH, because previously reported cases as familial idiopathic ONFH due to COL2A1 mutations corresponded to neither‐associated ONFH . Generally, bilateral involvement, early‐onset, and family history are the expected findings in bone diseases with stronger genetic effects.…”
Section: Methodsmentioning
confidence: 99%
“…Its mutations are known to cause failure of cartilage development and growth, prominently resulting in spinal deformity and epiphyseal dysplasia of the femoral head. So far, four COL2A1 mutations in six families have been reported as the cause of familial idiopathic ONFH: c.3508G>A (p.Gly1170Ser, rs121912891) in four Chinese families: c.2149G>A (p.Gly717Ser, rs387906558) in one Chinese family; c.1888G>A (p.Gly630Ser) in one Chinese family; c.4148C>T (p.Thr1383Met, rs138498898) in one family (unknown race) . The c.3508G>A mutation was also identified in one Japanese family, of which the phenotype was reported as Legg–Calve–Perthes disease .…”
mentioning
confidence: 99%
“…Cleft palate and retinal detachment frequently associated, as in SEDc (183900). A distinctive radiographic feature is irregular sclerotic changes, described as “dappled” in the metaphyses of the long bonesSulko et al 2005; Shapiro et al 2006; Czarny-Ratajczak et al 2009 Spondyloperipheral dysplasia12q13.11 COL2A1 ADType II collagen271700Short stature, platyspondyly, mild biconcave disc (fish-mouth vertebrae), kyphosis, short ilia, horizontal acetabulae, flattened capital femoral epiphyses, acetabular spurs (infancy), very short distal phalanges (2nd, 3rd, 4th, 5th), short metacarpals (2nd, 3rd, 4th, 5th), cone-shaped epiphyses, brachydactyly “E-like” changes, short feet, short phalanges, short metatarsals (4th)Zankl et al 2004; Bedeschi et al 2011 Czech dysplasia, spondyloepiphyseal dysplasia with precocious OA 12q13.11 COL2A1 ADType II collagen609162Normal stature, mild platyspondyly, irregular vertebral endplates, narrow intervertebral disc spaces, irregular sclerotic acetabulae, flattened capital femoral epiphyses, narrow iliac wings, narrow short femoral neck, arthralgia, flexion contractures (knee), osteochondromatosis (knee), short metacarpals (4th–5th), onset of joint pain in childhood, waddling gait, hip replacement in early adulthood, hearing lossHoornaert et al 2007; Tzschach et al 2008; Matsui et al 2009 Avascular necrosis of the femoral head (ANFH)12q13.11 COL2A1 ADType II collagen608805Patients present with groin pain, onset of symptoms in 2nd to 5th decades of life, degeneration of hip joint, narrowing of joint space, avascular necrosis/cystic changes/sclerosis of femoral head, generalized osteoporosis (in some patients), mild scoliosis (in some patients)Liu et al 2005; Nishimura et al 2005; Su et al 2008; Kannu et al 2011; Li et al 2014 Legg-Calvé-Perthes disease (LCPD)12q13.11 COL2A1 ADType II collagen150600Disease onset between 6 and 9 years, short stature, necrosis of capital femoral epiphysis, more severe in females, more frequent in malesNishimura et al 2005; Miyamoto et al 2007; Su et al 2008; Li et al 2014 Otospondylomegaepiphyseal dysplasia (OSMED), Nance-Sweeney chondrodysplasia, chondrodystrophy with sensorineural deafness12q13.11 COL2A1 ARType II collagen215150Short stature, sensorineural hearing loss, epiphyseal dysplasia, premature OA , midface hypoplasia, increased lumbar lordosis, vertebral coronal clefts (newborn), enlarged odontoid (childhood), platyspondyly (childhood), joint contra...…”
Section: Mutations Leading To Cartilage Pathologymentioning
confidence: 99%
“…, hypochondrodysplasia or deforming, i.e. , spondyloepiphyseal dysplasia congenita (SEDc), Kniest dysplasias, and Stickler syndrome or may appear as mild knee and hip joint diseases (Nishimura et al 2005; Su et al 2008; Warman et al 2011; Arnold and Fertala 2013; Li et al 2014). The most frequent amino acid substitutions in collagen type II occur at the G position of the G-X-Y triplets; for instance, a G853E (p.G1053E) substitution was found in a patient with a lethal form of SED.…”
Section: Mutations In Collagen Type IImentioning
confidence: 99%